DINAMIKA EFIKASI DIRI PENGASUHAN IBU MELALUI KONTEN MEDIA SOSIAL: STUDI HUKUM ISLAM PADA FOLLOWERS INSTAGRAM @igdailyjour - Humairah Al Fatihah Nur Fajry; Zulhas'ari Mustafa; Andi Herawati (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2026)
Parenting self-efficacy is a crucial factor in shaping the quality of parental caregiving. One of its key sources is vicarious experience, obtained through observing others’ parenting practices, including through social media content such as Instagram. This study aims to examine the dynamics of maternal parenting self-efficacy among followers of the @igdailyjour account and to analyze it from the perspective of Islamic law. This research is a field study employing a qualitative approach with a case study method, using in-depth interviews and content observation as data collection techniques. The findings indicate that parenting content shared by the account contributes to strengthening mothers’ parenting self-efficacy, particularly in enhancing their confidence, understanding, and daily caregiving practices. The parenting approach presented reflects values that align with Islamic principles of caregiving, such as compassion, patience, and responsibility. From the perspective of Islamic law, the use of social media as a source of parenting information may be considered a form of ikhtiar (effort) in fulfilling parental responsibility, which is deemed permissible (mubah) as long as it does not contradict Islamic principles.